Electrolytic capacitor having a conductive polymer compound and method for manufacturing the same

JP2026165705APending Publication Date: 2026-10-14RUBYCON CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025058234
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0011】 本開示によれば、十分な容量及び低周波数域における十分な特性、特には十分なtanδ及びE.S.R特性を示す電解コンデンサを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165705000001_ABST
    Figure 2026165705000001_ABST
Patent Text Reader

Abstract

The objective is to provide an electrolytic capacitor that exhibits sufficient capacitance and characteristics in the low-frequency range. [Solution] A method for manufacturing an electrolytic capacitor, further comprising: (i) providing a capacitor element comprising an anode foil, a cathode foil, and a separator between them, wherein the cathode foil is made of an aluminum alloy containing 0.05% by mass or more of copper; (ii) preparing a conductive polymer compound dispersion or solution containing a conductive polymer compound and a dopant; (iii) impregnating the capacitor element with the conductive polymer compound dispersion or solution and drying it to form a solid electrolyte portion in the gap between the anode foil and the cathode foil; and (iv) sealing the capacitor element in an outer casing, and further performing a thermal modification treatment on the capacitor element with the formed solid electrolyte portion at a temperature of 90°C or higher.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a solid electrolytic capacitor having a conductive polymer compound and a method for manufacturing the same.

BACKGROUND ART

[0002] (Electrolytic capacitor having conductive polymer) Conventionally, solid electrolytic capacitors using a conductive polymer compound as a solid electrolyte are known. Such capacitors can exhibit low ESR properties and excellent low-temperature characteristics. Further, such capacitors can provide highly reliable capacitors by using a solid conductive polymer with high heat resistance as the electrolyte.

[0003] Further, electrolytic capacitors (hybrid type capacitors) using a conductive polymer compound and an electrolytic solution as electrolytes are known. Such capacitors are advantageous in terms of, for example, the capacity appearance rate in initial capacitor characteristics and film repairability.

[0004] In order to improve the characteristics of electrolytic capacitors having a conductive polymer compound, the use of alloy cathode foils and the like have been studied.

[0005] Patent Document 1 describes a method for manufacturing an aluminum foil for an electrolytic capacitor cathode, comprising cold-rolling an aluminum alloy having a copper content of 0.05 to 1.0% by weight, and then performing intermediate annealing within a temperature range of 320 to 450°C. According to Patent Document 1, it has been conventionally known that the addition of copper increases the capacitance of the alloy foil, and the reason for the increase is said to be that copper is uniformly dissolved as a solid solution in the aluminum matrix, making the potential noble, and as a result, uniform and high-density recesses are formed on the surface of the foil during electrolytic etching, increasing the surface area. Further, Patent Document 1 describes that in producing an aluminum alloy foil for an electrolytic capacitor cathode, performing a process that allows copper to form a solid solution as uniformly as possible is important for increasing the capacitance, and uniform solid solution formation is achieved by performing the thermal modification treatment surface soaking treatment at a high temperature.

[0006] Patent Document 2 describes an electrolytic capacitor comprising an anode having a dielectric oxide film, a cathode, a separator disposed between the anode and the cathode, and a conductive polymer and electrolyte held in the separator, wherein the cathode may be an alloy containing aluminum and 0.05% to 0.50% by weight of copper. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 63-303040 [Patent Document 2] Japanese Patent Publication No. 2021-163877 [Overview of the project] [Problems that the invention aims to solve]

[0008] Conventional electrolytic capacitors containing conductive polymer compounds, which use an aluminum alloy for the cathode foil, can achieve relatively high capacitance, but they have problems with insufficient characteristics in the low-frequency range, particularly in terms of resistance characteristics.

[0009] This disclosure aims to provide an electrolytic capacitor that exhibits sufficient capacitance and sufficient characteristics in the low-frequency range, particularly sufficient tanδ and ESR characteristics. [Means for solving the problem]

[0010] The present invention can solve the above problems in the following embodiments. <Aspect 1> A method for manufacturing electrolytic capacitors, (i) To provide a capacitor element comprising an anode foil, a cathode foil, and a separator between them, wherein the cathode foil is made of an aluminum alloy containing 0.05% by mass or more of copper, (ii) Prepare a dispersion or solution of conductive polymer compounds containing conductive polymer compounds and dopants. (iii) Impregnating the capacitor element with the conductive polymer compound dispersion or solution and drying it to form a solid electrolyte portion in the gap between the anode foil and the cathode foil, (iv) Enclosing the capacitor element within the outer casing, Includes, The capacitor element on which the solid electrolyte portion is formed is further subjected to thermal modification treatment at a temperature of 90°C or higher. method. <Aspect 2> The method according to embodiment 1, further comprising introducing a liquid substance into the capacitor element on which the solid electrolyte portion is formed, so that the liquid substance is present between the anode foil and the cathode foil. <Aspect 3> The method according to embodiment 1 or 2, wherein the thermal reforming treatment is performed after (iv). <Aspect 4> The method according to any one of embodiments 1 to 3, wherein the thermal reforming treatment is performed at 100°C to 200°C. <Aspect 5> The method according to any one of embodiments 1 to 4, wherein the thermal reforming treatment is carried out for 10 to 200 minutes. <Aspect 6> The method according to any one of embodiments 1 to 5, wherein the cathode foil contains 0.05 to 1.0% by mass of copper. <Aspect 7> The method according to any one of embodiments 1 to 6, wherein the cathode foil is subjected to a chemical conversion treatment in the case of (i) above. <Aspect 8> The method according to any one of embodiments 1 to 7, wherein the conductive polymer compound and the dopant contained in the solid electrolyte portion form fine particles. <Pattern 9> An electrolytic capacitor manufactured by the method described in any of embodiments 1 to 8. [Effects of the Invention]

[0011] According to the present disclosure, it is possible to provide an electrolytic capacitor that exhibits sufficient capacitance and sufficient characteristics in the low frequency range, in particular sufficient tanδ and E.S.R. characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] [Figure 1] FIG. 1 shows an example of a method for manufacturing an electrolytic capacitor. [Figure 2] FIG. 2 shows the results related to a capacitor characteristic test of an example of the electrolytic capacitor according to the present invention. [Figure 3a] FIG. 3a is a schematic cross-sectional view of a solid electrolytic capacitor according to one embodiment of the present disclosure. [Figure 3b] FIG. 3b is a schematic perspective view of a capacitor element according to one embodiment of the present disclosure. [Figure 4] FIG. 4 is a schematic cross-sectional view of a main part of an electrolytic capacitor. DETAILED DESCRIPTION OF EMBODIMENTS FOR CARRYING OUT THE INVENTION

[0013] <Method for Manufacturing Electrolytic Capacitor> The method for manufacturing an electrolytic capacitor according to the present invention comprises: (i) providing a capacitor element comprising an anode foil having an oxide film formed on a surface thereof, a cathode foil, and a separator therebetween, wherein the cathode foil is made of an aluminum alloy containing 0.05 mass% or more of copper; (ii) preparing a conductive polymer compound dispersion or solution containing a conductive polymer compound and a dopant; (iii) impregnating the capacitor element with the conductive polymer compound dispersion or solution, and drying the same to form a solid electrolyte portion in gaps between the anode foil and the cathode foil; and (iv) enclosing the capacitor element in an exterior body; and further comprising subjecting the capacitor element on which the solid electrolyte portion has been formed to a thermal modification treatment at a temperature of 90°C or higher.

[0014] ​As described above, conventional electrolytic capacitors containing conductive polymer compounds that use an aluminum alloy for the cathode foil can achieve relatively high capacitance, but they have the disadvantage of having insufficient characteristics in the low-frequency range, particularly in terms of resistance characteristics.

[0015] In contrast, in the present invention, a solid electrolyte portion containing a conductive polymer compound is formed in a capacitor element having an aluminum alloy cathode foil, and then the electrolytic capacitor is subjected to a thermal modification treatment at 90°C or higher. According to the present invention, it is possible to provide a capacitor that has sufficient capacitance and sufficient characteristics in the low frequency range, in particular sufficient tanδ and ESR characteristics.

[0016] The method for manufacturing the electrolytic capacitor of the present invention will be described with reference to the drawings. The drawings are illustrative and do not limit the present invention. The drawings are not to scale.

[0017] Figure 1 shows one embodiment of the method for manufacturing an electrolytic capacitor according to the present invention. In the method shown in Figure 1, first, an electrolytic capacitor element 20 is provided (Figure 1(a)). Next, in Figure 1, the electrolytic capacitor element 20 is immersed in a chemical solution 50 in a chemical solution tank, and a predetermined voltage (e.g., 100V) is applied between the anode lead 30 and the chemical solution (Figure 1(b)). This operation repairs oxide film defects present at the ends of the anode foil 21 (see Figure 4) and oxide film defects that may be present on the surface. Then, in Figure 1, the electrolytic capacitor element 20 is dried (Figure 1(c)).

[0018] In the method shown in Figure 1, a conductive polymer compound dispersion 51 is prepared and impregnated into the electrolytic capacitor element 20 (Figure 1(d)). The conductive polymer compound dispersion contains a conductive polymer compound and a dopant. Instead of the conductive polymer compound dispersion, a solution of the conductive polymer compound dissolved in a solvent (conductive polymer compound solution) may be used. In Figure 1, the electrolytic capacitor element 20 removed from the conductive polymer compound dispersion 51 is dried, thereby forming a solid electrolyte portion (not shown) between the anode foil and the cathode foil (Figure 1(e)). At this point, the electrolytic capacitor element 20 with the solid electrolyte portion formed may be further immersed in a liquid substance 27 to introduce the liquid substance into the gap between the anode foil and the cathode foil (Figure 1(e-1)).

[0019] Then, in the method shown in Figure 1, the sealing member 40 is attached to the electrolytic capacitor element 20 (Figure 1(f)), the electrolytic capacitor element 20 is placed inside the metal case 10 (Figure 1(g)), and the metal case 10 is crimped near the open end to seal it (Figure 1(h)). The sealing member 40 can be made of rubber or a rubber composite material. After that, as shown in Figure 1, an aging process is performed by applying a predetermined voltage in a high-temperature atmosphere as desired (not shown).

[0020] According to the method of the present invention, after drying in (e), i.e., after the formation of the solid electrolyte portion, a thermal modification treatment is performed at 90°C or higher (for example, at the timing of HT1 in Figure 1). When a liquid substance is introduced as in (e-1), it is preferable to perform the thermal modification treatment after sealing in (h) (for example, at HT1 in Figure 1). This reduces the risk of deterioration of the liquid substance caused by the thermal modification treatment. In one preferred embodiment, the thermal modification treatment is performed after the aging treatment.

[0021] Although not limited by theory, there is a tendency for the resistance value to be higher at low frequencies than at high frequencies, and this is thought to be mainly due to the resistance of the conductive parts within the foil pits. In conventional electrolytic capacitors that use aluminum alloy cathode foil containing copper, the copper contained in the aluminum alloy and the conductive polymer have a junction and are in a conductive state, so the resistance of the conductive parts is picked up, which is thought to increase the resistance value at low frequencies.

[0022] In contrast, according to the present invention, after forming a solid electrolyte portion in a capacitor element having an aluminum alloy cathode foil, the electrolytic capacitor is subjected to a thermal modification treatment. This yields an electrolytic capacitor that has sufficient capacitance and sufficient characteristics in the low-frequency range, particularly sufficient tanδ and ESR characteristics. Although there is no intention to limit the theory, in this case, it is thought that the conductivity between copper and the conductive polymer is eliminated, thereby yielding an electrolytic capacitor that has sufficient capacitance and sufficient characteristics (particularly sufficient tanδ and ESR characteristics) during low-frequency measurements. The reason why the conductivity between copper and the conductive polymer is eliminated is not entirely clear, but it is thought that the thermal modification treatment breaks the relatively weak bond between copper and the conductive polymer. It is presumed that the thermal modification treatment contributes to the breaking of the above bond, for example, through the expansion and / or contraction of the conductive polymer, convection of the intervening liquid (e.g., liquid substance), and / or reaction between the surface of a metal such as copper or iron and the intervening liquid.

[0023] The steps of the present invention will be described in more detail below.

[0024] <Process (i): Capacitor element supply process> The present invention includes a method for manufacturing a capacitor element comprising an anode foil, a cathode foil, and a separator between them, wherein the cathode foil is made of an aluminum alloy containing 0.05% by mass or more of copper (capacitor element provision step).

[0025] The process of supplying this capacitor element is explained exemplified below.

[0026] First, an aluminum foil is provided as the anode foil 21. After roughening the surface of the aluminum foil by a surface expansion treatment, a predetermined voltage of 2V to 500V is applied to the roughened surface of the aluminum foil to perform a chemical conversion treatment, thereby forming an oxide film 22 on the surface of the aluminum foil. Then, a capacitor element is fabricated comprising the anode foil 21 having the oxide film 22, a cathode foil 23, and a separator 25 disposed between the anode foil 21 and the cathode foil 23 (see Figure 3b). Specifically, the capacitor element 20 is fabricated by overlapping and winding the anode foil 21, which has an uneven surface (rough surface) and on which the oxide film 22 is formed, and the cathode foil 23, which has an uneven surface, via the separator 25. At this time, a lead 30 is connected to the anode foil 21 and a lead 29 is connected to the cathode foil 23.

[0027] Next, the capacitor element 20 is immersed in the chemical conversion solution in the chemical conversion solution tank, and a predetermined voltage (e.g., 100V) is applied between the anode lead 30 and the chemical conversion solution for 5 minutes. This operation repairs oxide film defects present at the edges of the anode foil 21 and any oxide film defects that may be present on the surface.

[0028] As the chemical conversion solution, an aqueous solution of adipic acid, ammonium adipate, boric acid, ammonium borate, phosphoric acid, ammonium dihydrogen phosphate, ammonium hydrogen phosphate, ammonium phosphate, ammonium glutarate, ammonium azelaate, ammonium tartrate, ammonium sebacate, ammonium pimephosphate, ammonium suberate, decanedicarboxylic acid, ammonium decanedicarboxylic acid, long-chain dicarboxylic acid, long-chain ammonium dicarboxylic acid, etc. can be used.

[0029] (Cathode foil) The capacitor element according to this disclosure has a cathode foil made of an aluminum alloy containing 0.05% by mass or more of copper. This makes it possible to obtain an electrolytic capacitor with a relatively high capacitance.

[0030] The aluminum alloy of the cathode foil preferably contains 0.05 to 1.0 mass%, 0.07 to 0.5 mass%, or even 0.1 to 0.3 mass% of copper. The cathode foil may contain aluminum and / or copper alone, or aluminum and / or copper as a compound.

[0031] The copper content can be measured by ICP emission spectrometry.

[0032] Aluminum alloys may contain metals other than copper, such as iron, zinc, titanium, nickel, and lead. For example, iron may be present in an amount of 0.01 to 1.0 mass%, zinc and titanium may be present in an amount of 0.001 to 0.1 mass%, and nickel and zinc may be present in an amount of 0.0001 to 0.005 mass%.

[0033] The content of other metals can be measured by ICP emission spectrometry.

[0034] The cathode foil may have an oxide film formed on its surface. For example, the surface of the cathode foil may be roughened by etching, similar to the anode foil, and then an oxide film may be formed by natural oxidation. Alternatively, the cathode foil may be subjected to a chemical conversion treatment at a desired voltage (e.g., 2V), which may also form an oxide film.

[0035] (Anode foil) The capacitor element according to this disclosure has an anode foil on which an oxide film is formed on its surface.

[0036] The anode foil may be formed from a valve metal such as aluminum, tantalum, or niobium. Preferably, the anode foil is made of aluminum.

[0037] The anode foil has an oxide film on its surface. For example, an oxide film can be formed on the surface of the anode foil by roughening the surface by etching according to known methods, expanding the surface by sintering fine particles, and then performing a chemical conversion treatment.

[0038] <Separator> The capacitor relating to this disclosure may include a separator. The separator is disposed between the anode foil and the cathode foil.

[0039] Preferably, the separator is made of conductive polymer particles, cellulose fibers that are chemically compatible with water-soluble polymers, or synthetic resins such as nylon, PET, and PPS that have excellent heat resistance. For example, heat-resistant cellulose paper or heat-resistant flame-retardant paper can be used. More specifically, examples of separators include cellulose and mixed papers such as kraft, Manila hemp, esparto, hemp, and rayon; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and their derivatives; polytetrafluoroethylene resins; polyvinylidene fluoride resins; vinylon resins; polyamide resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide resins; polyethylene resins; polypropylene resins; trimethylpentene resins; polyphenylene sulfide resins; acrylic resins; and polyvinyl alcohol resins. These resins can be used individually or in mixtures.

[0040] <Process (ii): Process for preparing a dispersion or solution of conductive polymer compound> The manufacturing method of the present invention includes preparing a conductive polymer compound dispersion or solution containing a conductive polymer compound and a dopant (conductive polymer compound dispersion or solution preparation step).

[0041] (Dispersion or solution of conductive polymer compounds) A conductive polymer compound dispersion or solution contains a conductive polymer compound and a dopant. A conductive polymer-containing dispersion means a dispersion in which a conductive polymer compound and an optional dopant are dispersed in a dispersion medium. As the dispersion medium for a conductive polymer-containing dispersion, for example, water, protic solvents such as alcohol (e.g., methanol, ethanol, 1-propanol, butanol), and mixtures thereof can be used. A conductive polymer compound solution may be used instead of a conductive polymer-containing dispersion, in which case, as the solvent for the conductive polymer compound solution, for example, water, protic solvents such as alcohol (e.g., methanol, ethanol, 1-propanol, butanol), and mixtures thereof can be used.

[0042] A conductive polymer compound dispersion can be produced, for example, by polymerizing a suspended monomer (e.g., PEDOT monomer) (radical polymerization or oxidative polymerization) to create a conductive polymer compound (e.g., PEDOT polymer) to which dopants and emulsifiers have been added, and then dispersing the conductive polymer compound in a predetermined dispersion medium. The average particle size of the conductive polymer compound can be adjusted by appropriately setting the polymerization reaction conditions (e.g., concentrations of initiators, monomers, polymerization aids, etc., reaction temperature, stirring conditions of the reaction solution, etc.). It can also be adjusted by known grinding treatments (e.g., stirring grinding, vibration grinding, etc.). Furthermore, the particle size can be made uniform by preparative filtration.

[0043] As a specific example of a method for preparing a conductive polymer compound dispersion, the preparation procedure (a) to (e) for a PEDOT / PSS fine particle dispersion is shown below: (a) Prepare a PEDOT / PSS fine particle dispersion (e.g., 2% by mass) using ethylenedioxythiophene (EDOT) monomer and polystyrene sulfonic acid (PSS). (i) Remove excess cationic and / or anionic components by ion exchange treatment. (c) The process is carried out using a rotary homogenizer or an ultrasonic homogenizer to produce fine particles. (e) Adjust the pH to 2-5 by neutralization treatment. (e) Add a high-boiling point compound to the PEDOT / PSS fine particle dispersion. This may improve conductivity.

[0044] Steps (a) through (e) may be carried out according to conventional methods.

[0045] (conductive polymer) Examples of conductive polymers (conductive polymer compounds) include at least one selected from polythiophene, polypyrrole, and polyaniline, as well as their derivatives. The conductive polymer may be at least one of these. Preferably, the conductive polymer is a polymer of EDOT and its derivatives. Particularly preferred conductive polymers are polyethylenedioxythiophene (PEDOT) (especially poly(3,4-ethylenedioxythiophene)).

[0046] In one embodiment, the conductive polymer contained in the conductive polymer-containing dispersion is in the form of fine particles. This allows the conductive polymer-containing dispersion to penetrate sufficiently into the capacitor element, resulting in an electrolytic capacitor with good capacitor characteristics.

[0047] The average particle size of the particulate conductive polymer may be 1 nm to 600 nm, preferably 1 nm to 300 nm, or even more preferably in the range of 5 nm to 200 nm (e.g., 20 nm). The average particle size of the particulate conductive polymer can be determined, for example, from the particle size distribution obtained by dynamic light scattering.

[0048] (Dopant) The conductive polymer-containing dispersion further contains a dopant. The dopant may be a polyanion. Specific examples of dopants include aromatic sulfonic acids such as benzenesulfonic acid or its derivatives, naphthalenesulfonic acid or its derivatives, and anthraquinonesulfonic acid or its derivatives; polymeric sulfonic acids such as polystyrene sulfonic acid (PSS), sulfonated polyesters, phenolsulfonic acid novolac resins, and copolymers of styrenesulfonic acid and non-sulfonic monomers (such as methacrylic acid esters, acrylic acid esters, unsaturated hydrocarbon-containing alkoxysilane compounds or their hydrolysates); and chain-like sulfones such as methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, and butanesulfonic acid. These may be used individually or in combination of two or more.

[0049] Polystyrene sulfonic acid (PSS) with a weight-average molecular weight of 10,000 to 1,000,000 is preferred.

[0050] In a particularly preferred embodiment, the conductive polymer-containing dispersion comprises polyethylenedioxythiophene (PEDOT) as the conductive polymer compound and polystyrene sulfonic acid (PSS) as the dopant.

[0051] The conductive polymer compound and the polyanion dopant may have a particulate shape. The average particle size of the fine particles composed of the conductive polymer compound and the polyanion dopant may be 1 nm to 1 μm or 1 nm to 600 nm, preferably in the range of 1 nm to 300 nm, or even more preferably in the range of 5 nm to 200 nm (e.g., 20 nm). The average particle size of the fine particles composed of the conductive polymer and the polyanion dopant can be determined, for example, from the particle size distribution by dynamic light scattering.

[0052] (Second Dopant) The conductive polymer-containing dispersion may further contain a secondary dopant different from the dopant described above. The secondary dopant may act as an conductivity enhancer. The secondary dopant may be a particle-penetrating liquid (particularly a liquid that penetrates conductive polymer-containing particles), and this liquid may penetrate and fill the inside of the particles (particularly conductive polymer-containing particles), moving the molecular chains of the conductive polymer, thereby promoting stacking of the conductive polymer particles, and consequently improving conductivity. Furthermore, the secondary dopant may have a swelling effect. That is, by containing a secondary dopant, the solid electrolyte constituting the solid electrolyte portion in the electrolytic capacitor (for example, fine particles formed from a conductive polymer compound and a dopant) may swell, thereby expanding the internal space of the particles and further improving conductivity. Therefore, the secondary dopant is particularly a swelling agent. The secondary dopant may be a polar organic solvent or organic compound with a boiling point of 150°C or higher, or a liquid polymer compound without a boiling point, such as a polymer having a polyether structure, and may have a weight-average molecular weight of 100 to 10000 (measured by gel filtration chromatography). Specific examples of secondary dopants include glycerin, diglycerin, triglycerin, tetraglycerin, polyglycerin, polyglyceryl ether, diethylene glycol, triethylene glycol, and polyethylene glycol. These can function as solid electrolytes when incorporated into conductive polymers.

[0053] In an exemplary embodiment, PSS acts as a counterion (Dope agent) that stabilizes the polarons (+holes) of PEDOT formed during the polymerization of PEDOT (it is contained in the polymer). Furthermore, the conductivity is improved by adding high-boiling point solvents such as polyethylene glycol and glycerin as secondary dopants to this particulate PEDOT / PSS. Although not limited by theory, this phenomenon is thought to be caused by the swelling of PEDOT / PSS particles (imagine a ball-like structure of PSS, with PEDOT partially attached to the threads of PSS) in a solvent, etc., forming a stacking (layered arrangement) inter-particle structure similar to the crystallization of PEDOT, thereby promoting electronic conductivity. The swollen PEDOT / PSS particles then solidify as a solid electrolyte.

[0054] The mass content of the secondary dopant may be 1 to 20 times, 1 to 10 times, 1 to 5 times, or even 1 to 2 times, relative to the total amount of the conductive polymer compound and the above-mentioned dopant.

[0055] <Step (iii): Solid electrolyte part formation step> The manufacturing method of the present invention includes impregnating a capacitor element with a conductive polymer compound dispersion or solution and drying it to form a solid electrolyte portion in the gap between the anode foil and the cathode foil (solid electrolyte portion formation step). In this disclosure, "the gap between the anode foil and the cathode foil" includes not only "the gap between the anode foil and the separator and the gap between the cathode foil and the separator" but also "the gap between fibers within the separator". Furthermore, "the gap between the anode foil and the cathode foil" also includes "the gap in etching pits (recesses) formed on the surface of the anode foil or cathode foil by roughening through etching".

[0056] For example, a capacitor element is immersed in a conductive polymer compound dispersion or conductive polymer compound solution using an introduction tank. Then, the capacitor element is removed from the conductive polymer compound dispersion or solution and heat-treated to form a solid electrolyte between the anode foil and the cathode foil. This operation can be repeated multiple times, thereby increasing the amount of solid electrolyte filled.

[0057] The solid electrolyte portion can be formed, for example, by an immersion impregnation method. That is, after filling an introduction tank with a conductive polymer compound dispersion (for example, a conductive polymer compound concentration of 2% by mass), the capacitor element is immersed in the conductive polymer compound dispersion. Next, the capacitor element is removed from the introduction tank, and then the capacitor element is heat-treated and dried. This allows the solid electrolyte to be introduced into the gap between the anode foil 21 and the cathode foil 23, thereby forming an electrolyte portion on the oxide film.

[0058] Furthermore, in order to increase the proportion of solid electrolyte in the voids, the number of repetitions of the above operation can be increased, and / or the polymer concentration in the conductive polymer compound dispersion can be increased. On the other hand, in order to decrease the proportion of solid electrolyte in the voids, the number of repetitions of the above operation can be decreased, and / or the polymer concentration in the conductive polymer compound dispersion can be decreased.

[0059] The impregnated capacitor element may be dried at 100°C to 180°C for 10 to 120 minutes. This drying process removes at least partially the liquid components (particularly the dispersion medium or solvent) contained in the solid electrolyte. Preferably, this drying process reduces the amount of dispersion medium or solvent (particularly water) contained in the solid electrolyte to 10% by mass or less, or even 2% by mass or less, relative to the entire solid electrolyte, thereby forming a solid electrolyte between the anode foil and the cathode foil.

[0060] (Solid electrolyte section) The solid electrolyte portion, composed of a solid electrolyte, is in at least partial contact with the oxide film formed on the surface of the anode foil. The solid electrolyte portion contains a conductive polymer compound and a dopant, and further contains an amphoteric compound having both an acidic group and a basic group in one molecule.

[0061] The solid electrolyte portion may take various forms, for example, a continuous, uniform thick or thin layer, a film, or an aggregate of fine particles, or a network of fine particle chains. In particular, the solid electrolyte portion may take the form of a layer of fine particles composed of fine particles containing a conductive polymer compound and a dopant.

[0062] The solid electrolyte portion is in direct contact with the oxide film of the anode foil, at least partially, and in direct contact with the metal surface and / or oxide film of the cathode foil, at least partially.

[0063] (Liquid substance) In one embodiment, the manufacturing method of the present invention may include, after the solid electrolyte portion formation step, introducing a liquid substance into the capacitor element in which the solid electrolyte portion is formed, so that the liquid substance is present between the anode foil and the cathode foil. The liquid substance may, in particular, be present so as to surround the solid electrolyte (in particular the conductive polymer compound-containing fine particles constituting the solid electrolyte portion).

[0064] The method of the present invention is particularly effective when using a liquid substance, and yields an electrolytic capacitor with even better characteristics in the low-frequency range, and in particular, even better tanδ and ESR characteristics. Although not limited by theory, when using a liquid substance, it is conceivable that convection of the liquid substance occurs during the thermal reforming treatment, causing the junction between the metal such as copper or iron and the conductive polymer to break and reducing conductivity, and as a result, tanδ and ESR in the low-frequency range to be suppressed.

[0065] From the viewpoint of film repair, an electrically neutral and polar liquid substance (solvent) is preferred. This solvent is less affected by the repulsion due to the surface charge of the PEDOT / PSS particles, so it penetrates into the interior and even moves to the outside of the particles. Furthermore, since an oxygen-containing polar solvent can be supplied, film formation is performed with high efficiency. Examples of such solvents include proton-based high-boiling-point polar solvents with a boiling point of 150°C or higher, such as ethylene glycol, diethylene glycol, triethylene glycol, glycerin, and their derivatives, as well as polymer solutions of polyethylene glycol, polyalkylene glycol, polyglycerin, polyoxyalkylene polyglyceryl ether, and their derivatives.

[0066] In the capacitor according to this disclosure, the proportion of liquid material in the gap between the anode foil and the cathode foil may be 10 vol% to 99 vol%, particularly 50 vol% to 99 vol%, or even 70 vol% to 99 vol%.

[0067] The liquid substance is not particularly limited, but may include, for example, organic solvents, especially polymeric organic solvents. The liquid substance may include, for example, water, hydrophilic polymer compounds, components having hydroxyl groups, such as polyoxyalkylenes and their derivatives (polyglycerin), water-soluble polyurethanes, water-soluble polyesters, water-soluble polyamides, water-soluble polyimides, water-soluble polyacrylics, water-soluble polyacrylamides, water-soluble silicones, polyvinyl alcohols, polyacrylic acid, or mixtures thereof.

[0068] In particular, the components of the liquid substance include glycol compounds, such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, and other polyethylene glycols, as well as their derivatives, glycerin and diglycerin, as well as their derivatives, γ-butyrolactone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, and dimethylformamide. These may be used individually or in combination of two or more. Of these, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, other polyethylene glycols, and their derivatives are preferred, with ethylene glycol and diethylene glycol being the most preferred. When ethylene glycol and / or diethylene glycol are used as the liquid substance, electrolytic capacitors with particularly good reflow characteristics can be obtained.

[0069] A liquid substance is, for example, a liquid that can hold acidic and basic components. In particular, a liquid substance is a solvent in which acidic and basic components can be dissolved as solutes.

[0070] In particular, the liquid substance contains glycol compounds (particularly ethylene glycol and / or diethylene glycol) in a total proportion of 30% to 99% by mass, 50 to 95% by mass, or even 60% to 80% by mass. In one particular embodiment, the liquid substance also contains glycol compounds (particularly ethylene glycol and / or diethylene glycol) in a total proportion of 90% to 100% by mass, 90 to 99.9% by mass, or even 95% to 99.5% by mass.

[0071] <Water> The liquid substance may contain water.

[0072] When the liquid substance present in the void between the anode foil and the cathode foil contains "water," particularly good effects can be obtained in reducing the defect density of the oxide film and reducing leakage current.

[0073] The method of the present invention is particularly effective when the liquid substance contains water, and can yield electrolytic capacitors with even better characteristics in the low-frequency range, and in particular, even better capacitor characteristics (especially tanδ and ESR characteristics) in the low-frequency range. Although not limited by theory, when the liquid substance contains water, the convection of the liquid substance during the thermal reforming treatment becomes relatively vigorous, and the pressure due to the evaporation of water causes the junction between the metal such as copper or iron and the conductive polymer to break, resulting in a loss of conductivity and suppression of tanδ and ESR in the low-frequency range.

[0074] The water content may be 0% to 10% by mass relative to the liquid substance, preferably 0.1% to 10% by mass, and more preferably 0.5% to 5% by mass. When the water content is within this range, the effect of repairing defects in the oxide film can be sufficiently obtained, and adverse effects caused by excessive water content (such as expansion of the capacitor that may occur when used for a long period of time in a high-temperature environment) can be avoided or suppressed.

[0075] Furthermore, when an electrolytic capacitor containing a solid electrolyte also contains a liquid substance, the electrolytic capacitor can specifically be called a hybrid electrolytic capacitor.

[0076] The liquid substance may contain acidic and basic components. These acidic and basic components are different substances from the amphoteric compounds according to the present invention described above, and do not satisfy the above requirements for amphoteric compounds.

[0077] Examples of acidic components include organic acids, inorganic acids, and complex compounds thereof.

[0078] Examples of organic acids include carboxylic acids, phenols, and sulfonic acids. Examples of carboxylic acids include formic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, sulfosalicylic acid, maleic acid, adipic acid, benzoic acid, triylic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcinic acid, phloroglucinic acid, gallic acid, and citric acid.

[0079] Examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid.

[0080] Examples of complex compounds of organic and inorganic acids include borodisalicylic acid, borodisuoic acid, and borodiglycolic acid.

[0081] The acidic components described above may be used individually or in combination of two or more.

[0082] The acidic component is contained, for example, at a concentration of 2.6% to 20% by mass relative to the liquid substance.

[0083] The basic component may be one or more selected from amines, amidines, and ammonia, and is preferably an amine.

[0084] The basic component may be present in an amount of 0.2% to 20% by mass relative to the liquid substance.

[0085] (Thermal modification treatment) The manufacturing method of the present invention further includes, after the solid electrolyte formation step, performing a thermal modification treatment at 90°C or higher on the capacitor element on which the solid electrolyte is formed. The thermal modification treatment is performed after the solid electrolyte formation step. According to the present invention, by subjecting a capacitor element having an aluminum alloy cathode foil to thermal modification treatment, a capacitor can be obtained that has sufficient capacitance and sufficient characteristics in the low frequency range, in particular sufficient tanδ and ESR characteristics.

[0086] In one embodiment, a thermal modification treatment is performed after sealing in the outer casing (HT1 in Figure 1). By performing a thermal modification treatment after sealing, an electrolytic capacitor with better capacitor characteristics (especially tanδ and ESR) in the low-frequency range can be obtained. Although not limited by theory, since conductivity between copper and conductive polymer is particularly easily established by stress during sealing, it is presumed that performing a thermal modification treatment after sealing, where there is no stress, will make the modification of the solid electrolyte and / or cathode foil even more effective.

[0087] When introducing a liquid substance into a capacitor element, it is preferable to perform the thermal modification treatment after the sealing process (HT1 in Figure 1). This reduces the risk of deterioration of the liquid substance caused by the thermal modification treatment.

[0088] In one embodiment, the thermal reforming treatment may be carried out at 92°C or higher, 94°C or higher, 95°C or higher, 96°C or higher, 98°C or higher, 100°C or higher, 105°C or higher, 110°C or higher, 115°C or higher, 120°C or higher, 125°C or higher, 130°C or higher, or 140°C or higher and / or 200°C or lower, 170°C or lower, 160°C or lower, 155°C or lower, or 150°C or lower. Preferably, the thermal reforming treatment is carried out at 90°C to 200°C, 100°C to 170°C, 110°C to 160°C, 120°C to 160°C, or even 125°C to 150°C. In this case, an electrolytic capacitor with particularly good capacitor characteristics (especially tanδ and ESR characteristics) in the low frequency range can be obtained.

[0089] In one embodiment, the thermal reforming treatment is carried out for a period of 10 minutes or more, 40 minutes or more, or 90 minutes or more and / or 200 minutes or less, 150 minutes or less, or 100 minutes or less. Preferably, the thermal reforming treatment is carried out for a period of 10 minutes to 200 minutes, or even more preferably 40 minutes to 150 minutes.

[0090] In particular, thermal reforming treatment: This may be carried out at a temperature of 90°C to 120°C or 90°C to 110°C for 80 minutes to 180 minutes or 120 minutes to 170 minutes, or This may be carried out at a temperature of 105°C to 145°C or 115°C to 135°C for 30 minutes to 160 minutes or 60 minutes to 150 minutes, or The thermal modification process may be carried out at temperatures of 130°C to 170°C, 140°C to 160°C, or 145°C to 155°C for 5 to 70 minutes, 10 to 60 minutes, 10 to 50 minutes, 10 to 40 minutes, 10 to 30 minutes, or 10 to 20 minutes. By performing the thermal modification treatment in these temperature and time combinations, the risk of capacitor degradation due to excessive thermal modification treatment is reduced, while electrolytic capacitors with particularly good capacitor characteristics (especially tanδ and ESR characteristics) in the low-frequency range can be obtained. Furthermore, the higher the temperature, the shorter the thermal modification treatment time required to obtain electrolytic capacitors with good capacitor characteristics, leading to an increase in production efficiency.

[0091] In one embodiment, the thermal reforming treatment is carried out at a temperature of 120°C or higher, 125°C or higher, 130°C or higher, 140°C or higher, 145°C or higher, 150°C or higher, 155°C or higher, 160°C or higher, or 165°C or higher and / or 200°C or lower, 195°C or lower, 190°C or lower, 185°C or lower, 180°C or lower, 175°C or lower, or 170°C or lower. In this case, the thermal reforming treatment can be carried out in a particularly short time, for example, in 60 minutes or less, 50 minutes or less, 40 minutes or less, 30 minutes or less, 25 minutes or less, 20 minutes or less, 15 minutes or less, 10 minutes or less, 5 minutes or less, 4 minutes or less, 3 minutes or less, 2 minutes or less, 1 minute or less, or 30 seconds or less. The lower limit of the time in this case is not particularly limited, but may be, for example, 1 second or more or 10 seconds or more.

[0092] The method for performing the thermal reforming treatment is not particularly limited. For example, the thermal reforming treatment can be performed by placing a capacitor element having a solid electrolyte (e.g., an electrolytic capacitor after the sealing process) into a furnace set to a temperature for thermal reforming treatment and heating it for a predetermined time.

[0093] In one embodiment, the thermal reforming treatment may be carried out at a relative humidity of 0% to 90%, preferably 0% to 80%, and more preferably 0% to 75%. Alternatively, the thermal reforming treatment may be carried out in a constant temperature chamber (forced hot air circulation and ventilation system).

[0094] The thermal modification process is carried out without applying voltage. In this case, the degradation of the conductive polymer is suppressed, the resistance value does not tend to increase, and it has the advantages of simplifying the process, making equipment smaller and reducing costs.

[0095] <Sealing Process> The manufacturing method of the present invention includes encapsulating a capacitor element within an outer casing. This encapsulation process is described exemplified below.

[0096] In the sealing process, for example, the sealing member 40 is attached to the capacitor element 20, and after inserting the capacitor element 20 into the metal case 10, the metal case 10 is crimped near the open end of the metal case 10. As the sealing member 40, for example, isobutylene-isoprene rubber (IIR) can be used. Instead of isobutylene-isoprene rubber (IIR), rubber materials such as ethylene-propylene terpolymer (EPT), EPT-IIR blend rubber, silicone rubber, or rubber composite materials made by bonding resin and rubber, such as phenolic resin (Bakelite), epoxy resin, or fluororesin, can be used for sealing. Furthermore, the sealing rubber surface crimped using the sealing member can be coated with epoxy resin or the like by potting to enhance airtightness, sealing strength, and heat resistance. After that, an aging process is carried out by applying a predetermined voltage in a high-temperature atmosphere. This completes the electrolytic capacitor 1 according to the embodiment. The aging process that can be performed after the sealing process can generally be carried out under conditions such as a temperature of 20 to 85°C, a relative humidity of 0 to 90%, and the application of a predetermined voltage.

[0097] (Exterior) The outer casing is a component capable of housing capacitor elements, and has a cavity (empty space) and an opening for housing the capacitor elements.

[0098] In one embodiment of the present invention, the outer casing is made of metal. In this case, a capacitor with superior heat resistance and moisture resistance can be provided compared to a case where the outer casing is made of, for example, plastic material.

[0099] The shape of the casing is not particularly limited, but may be cylindrical, prismatic (especially rectangular), etc. For example, the casing has a bottom and sides, and these bottom and sides define the cavity. The casing may also have an opening in the part corresponding to the top surface. The capacitor element can be housed in the cavity through this opening. The cavity of the casing may have a size corresponding to the size of the capacitor element.

[0100] In one particularly preferred embodiment, the outer casing is a metal can, especially a steel can or an aluminum can.

[0101] <<Electrolytic Capacitor>> The present invention includes an electrolytic capacitor manufactured by the method according to the present invention described above. Details of the components of this electrolytic capacitor can be found in the above description of the method according to the present invention.

[0102] In one embodiment, the electrolytic capacitor according to the present invention may be the following: An electrolytic capacitor comprising an outer casing housing a capacitor element, The capacitor element has an anode foil, a cathode foil, and a separator between them, with an oxide film formed on their surfaces, the cathode foil is made of an aluminum alloy containing 0.05% by mass or more of copper, and a solid electrolyte portion is present in the void between the anode foil and the cathode foil. The solid electrolyte portion comprises a conductive polymer compound and a dopant. An electrolytic capacitor exhibiting a tanδ of 4.5% or less and / or an ESR of 200 mΩ or less at 120 Hz.

[0103] Details of each component in this embodiment (anode foil, cathode foil, separator, conductive polymer compound, and dopant, etc.), as well as their preferred range and preferred embodiment, can be found in the description of the manufacturing method of the present invention above.

[0104] Such electrolytic capacitors can be manufactured by the manufacturing method described above according to the present invention.

[0105] The electrolytic capacitor according to the present invention has a relatively high capacitance due to the presence of an alloy cathode foil, while also having good tanδ and / or ESR in the low frequency range.

[0106] In one embodiment, the electrolytic capacitor according to the present invention may have a tanδ of 0.1-4.0%, 0.1-3.5%, 0.1-3.0%, or 0.1-2.2%, and / or an ESR of 10-200mΩ, 20-200mΩ, 30-150mΩ, or 40-100mΩ.

[0107] The following are preferred embodiments of the electrolytic capacitor of the present invention: • An electrolytic capacitor has a liquid substance between the anode foil and the cathode foil. The conductive polymer compound and dopant contained in the solid electrolyte form fine particles.

[0108] <Configuration of electrolytic capacitor 1 according to the embodiment> Figure 3 is a diagram illustrating the electrolytic capacitor 1 according to the embodiment. Figure 3(a) is a cross-sectional view of the electrolytic capacitor 1, and Figure 3(b) is a perspective view of the capacitor element 20.

[0109] Figure 4 is a diagram illustrating the main parts of the electrolytic capacitor 1 according to this embodiment. Figure 2 is a cross-sectional view of the main parts of the electrolytic capacitor 1.

[0110] The electrolytic capacitor 1 according to this embodiment is a wound-type electrolytic capacitor, and as shown in Figure 1, comprises a bottomed cylindrical metal case 10, a capacitor element 20, and a sealing member 40.

[0111] The bottom of the metal case 10 is nearly circular in shape, and a valve (not shown) is provided near the center. Therefore, when the internal pressure rises, the valve can break, releasing the internal pressure to the outside. The side surfaces of the metal case 10 are erected almost perpendicularly to the outer edge of the bottom surface. The opening of the metal case 10 is sealed by a sealing member 40, and the two leads 29 and 30 of the capacitor element 20 are led out through a through-hole in the sealing member 40.

[0112] The capacitor element 20 is housed inside the metal case 10 and, as shown in Figures 3(b) and 4, comprises an anode foil 21, a cathode foil 23, and a separator 25 disposed between the anode foil 21 and the cathode foil 23, with the anode foil 21 and the cathode foil 23 overlapping and wound together via the separator 25.

[0113] In the embodiment shown in Figure 4, a solid electrolyte phase consisting of particulate conductive polymer compound 26 and a liquid substance phase 27 containing a liquid substance are introduced into the void between the anode foil 21 and the cathode foil 23, with the liquid substance phase 27 surrounding the solid electrolyte consisting of the conductive polymer compound 26. The anode foil 21 and the cathode foil 23 have oxide films 22 and 24 on their surfaces, respectively. [Examples]

[0114] Embodiments of the present invention will be described in more detail below with reference to examples. The following examples and comparative examples are not intended to limit the present invention.

[0115] <<Examples 1-5 and Comparative Examples 1-4>> In Examples 1-5 and Comparative Examples 1-4, electrolytic capacitors with aluminum alloy cathode foil were fabricated under various thermal modification conditions, and their electrical characteristics were evaluated.

[0116] <Example 1> (Fabrication and evaluation of electrolytic capacitors) The procedure for fabricating and evaluating the electrolytic capacitor according to Example 1 includes the following: (1) A capacitor element was fabricated by winding an aluminum anode foil having a voltage-resistant coating corresponding to the capacitor's rated voltage and a cathode foil made of an aluminum alloy having the composition described in Table 1, with a cellulose separator in between. The cathode foil of the electrolytic capacitor in Example 1 was not chemically treated. (2) A dispersion in an aqueous solvent was prepared containing conductive polymer compound fine particles composed of 2.0% by mass of PEDOT and PSS and 15% by mass of triglycerin as a secondary dopant. Commercially available reagents were used. (3) The conductive polymer compound dispersion was impregnated into the capacitor element to form a solid electrolyte between the anode foil and the cathode foil, and then heated at 120°C for 60 minutes to dry. (4) A sealing member made of isobutylene-isoprene rubber was attached to the capacitor element, the capacitor element was inserted into an aluminum metal case, and the metal case was crimped and sealed near the open end of the metal case. (5) After performing an aging treatment under the conditions of relative humidity 25%, temperature 25°C, and voltage 25V, the capacitor element was subjected to a thermal modification treatment at 150°C for 60 minutes using a constant temperature chamber (forced hot air circulation and ventilation method) to obtain the electrolytic capacitor according to Example 1.

[0117] <Capacitor Characterization Evaluation> For the electrolytic capacitor obtained in Example 1, the ESR at 120 Hz and tanδ at 120 Hz were measured. Details and results of the obtained electrolytic capacitor are shown in Table 1 below.

[0118] In addition, Figure 2 shows the measurement results for ESR and tanδ, along with the measurement results for electrolytic capacitors obtained by varying the thermal reforming treatment time.

[0119] <Examples 2 and 3> Except for applying a chemical conversion treatment to the cathode foil, electrolytic capacitors according to Examples 2 and 3 were manufactured in the same manner as in Example 1, and the ESR at 120 Hz and tanδ at 120 Hz were measured and evaluated. The results are shown in Table 1 below.

[0120] <Example 4> An electrolytic capacitor according to Example 4 was manufactured in the same manner as in Example 1, except that the thermal reforming treatment was performed at 125°C for 150 minutes. The ESR and tanδ at 120Hz were measured and evaluated. The results are shown in Table 1 below. In addition, Figure 2 also shows the measurement results for ESR and tanδ, along with the measurement results for electrolytic capacitors obtained by varying the thermal reforming treatment time.

[0121] <Example 5> An electrolytic capacitor according to Example 5 was manufactured in the same manner as in Example 1, except that the thermal reforming treatment was performed at 100°C for 150 minutes. The ESR and tanδ at 120 Hz were measured and evaluated. The results are shown in Table 1 below. Figure 2 also shows the measurement results for ESR and tanδ, along with the measurement results for electrolytic capacitors obtained by varying the thermal reforming treatment time.

[0122] <Comparative Example 1> An electrolytic capacitor according to Comparative Example 1 was manufactured in the same manner as in Example 1, except that the thermal reforming treatment was performed at 85°C for 150 minutes. The ESR and tanδ at 120 Hz were measured and evaluated. The results are shown in Table 1 below. Figure 2 also shows the measurement results for ESR and tanδ, along with the measurement results for electrolytic capacitors obtained by varying the thermal reforming treatment time.

[0123] <Comparative Examples 2-4> Electrolytic capacitors according to Comparative Examples 2 to 4 were manufactured in the same manner as in Examples 1 to 3, except that thermal reforming treatment was not performed. The ESR and tanδ at 120 Hz were measured and evaluated. The results are shown in Table 1 below.

[0124] <Reference Examples 1-2 and Reference Comparison Examples 1-2> Reference Examples 1-2 and Reference Comparative Examples 1-2 are experimental examples using high-purity aluminum alloy. Electrolytic capacitors were manufactured in the same manner as in the above examples or comparative examples, and the ESR at 120 Hz and tanδ at 120 Hz were measured and evaluated. The results are shown in Table 2 below.

[0125] [Table 1]

[0126] [Table 2]

[0127] As can be seen in Table 1, Examples 1 to 5, which had an aluminum alloy cathode foil containing 0.05 mass% or more of copper and were subjected to thermal reforming treatment at 90°C or higher, all showed relatively suppressed tanδ and ESR compared to Comparative Example 1, which was subjected to thermal reforming treatment at 85°C, and Comparative Examples 2 to 4, which were not subjected to thermal reforming treatment. Furthermore, as can be seen from Tables 1 and 2, electrolytic capacitors having an aluminum alloy cathode foil containing 0.05 mass% or more of copper show relatively high capacitance compared to electrolytic capacitors having an aluminum alloy cathode foil containing less than 0.05 mass% of copper. Therefore, it can be seen that the electrolytic capacitor according to the present invention has relatively high capacitance and shows relatively suppressed tanδ and ESR by undergoing thermal reforming treatment at 90°C or higher.

[0128] Furthermore, in Reference Examples 1 and 2, which do not have alloy cathode foil, no particular suppression of tanδ and ESR was observed compared to Reference Comparative Examples 1 and 2, despite undergoing thermal modification treatment at 90°C or higher. Therefore, it can be seen that electrolytic capacitors with alloy cathode foil exhibit a tanδ and ESR suppression effect from thermal modification treatment at 90°C or higher, while electrolytic capacitors without alloy cathode foil do not.

[0129] Figure 2 shows the relationship between the change ratios of ESR and tanδ at 120 Hz and the time subjected to thermal reforming for electrolytic capacitors obtained by varying the thermal reforming treatment time.

[0130] Figure 2 shows that electrolytic capacitors subjected to heat treatment at 150°C, 125°C, and 100°C for a certain period of time exhibit relatively suppressed ESR and tanδ values ​​at 120 Hz. Furthermore, it can be seen that the higher the temperature of the heat reforming treatment, the more quickly the ESR and tanδ are suppressed.

[0131] The present invention is not limited to the embodiments described above, and various modifications are possible without departing from the scope of the present invention. [Explanation of Symbols]

[0132] 1 Electrolytic capacitor 10 Metal Cases 20 Capacitor elements 21 Anode foil 22, 24 Oxide film 23 Cathode foil 25 Separators 26 Solid electrolyte 27. Liquid substances 29, 30 Lead 40 Sealing material 50 Chemical liquid 51 Conductive polymer compound dispersion

Claims

1. A method for manufacturing electrolytic capacitors, (i) To provide a capacitor element comprising an anode foil, a cathode foil, and a separator between them, wherein the cathode foil is made of an aluminum alloy containing 0.05% by mass or more of copper, (ii) Prepare a dispersion or solution of conductive polymer compounds containing conductive polymer compounds and dopants. (iii) Impregnating the capacitor element with the conductive polymer compound dispersion or solution and drying it to form a solid electrolyte portion in the gap between the anode foil and the cathode foil, (iv) Enclosing the capacitor element within the outer casing, Includes, The capacitor element on which the solid electrolyte portion is formed is further subjected to thermal modification treatment at a temperature of 90°C or higher. method.

2. The method according to claim 1, further comprising introducing a liquid substance into the capacitor element on which the solid electrolyte portion is formed, so that the liquid substance is present between the anode foil and the cathode foil.

3. The method according to claim 1 or 2, wherein the thermal reforming treatment is performed after (iv).

4. The method according to claim 1 or 2, wherein the thermal modification treatment is performed at 100°C to 200°C.

5. The method according to claim 1 or 2, wherein the thermal reforming treatment is performed for 10 to 200 minutes.

6. The method according to claim 1 or 2, wherein the cathode foil contains 0.05 to 1.0% by mass of copper.

7. The method according to claim 1 or 2, wherein the cathode foil is subjected to a chemical conversion treatment in the case of (i) above.

8. The method according to claim 1 or 2, wherein the conductive polymer compound and the dopant contained in the solid electrolyte portion form fine particles.

9. An electrolytic capacitor manufactured by the method described in claim 1 or 2.

Citation Information

Patent Citations

  • Manufacture of aluminum-alloy foil for electrolytic capacitor cathode

    JP1988303040A

  • Electrolytic solution and electrolytic capacitor

    JP2021163877A